Stability of guanine-quadruplexes as sensing elements investigated using solvation free energy - Norhakim, N. (Institute of Electrical and Electronics Engineers Inc., 2021)
A guanine-quadruplex (G4) is a stack of guanine tetrads. Its structure varies significantly with the length of the guanine-rich DNA strand and the nature of the aqueous solution that surrounds it. It is an attractive candidate for sensing element in ion sensor applications due to its high specificity of binding to metal ions. A robust ion sensor, however, requires a stable G4 structure. Hence, in this work, the stability of several G4 structures is investigated by calculating the structure's free energy at several different ionic concentrations and temperatures. It is found that the most extended sequences of the G4 destabilize at low ions concentration and high solution temperatures. The results also indicate that the G4 used in this work retains its structure at a high ions concentration. The knowledge on G4 stability could help to develop ways to preserve G4 DNA which is necessary to ensure its reactivity in sensing applications. Â© 2021 IEEE.